Implementation of Regulations to Support Coastal Waste Management in Bali - Ripaldi, I Kadek Agus; Mberato, Shellyn Prastisia; Rahman, Muh. Soekarno Saputra; Rini, Indri Putri Sekar (Amcolabora, 2026)
Waste management is an important issue that remains a challenge in Indonesia. To address this issue, Bali has implemented various waste management programmes and regulations, including in coastal areas. However, the effectiveness of these programmes and regulations has not been maximised due to several obstacles. This study aims to analyse the implementation of waste management regulations in the coastal areas of Bali from 2020 to 2025. This study uses a qualitative descriptive approach with literature review and relevant observation methods. The data used is secondary data obtained from a review of recent scientific articles. The results show that Bali's coastal waste management regulations are not yet optimal due to issues such as a lack of coordination and collaboration among stakeholders, low public awareness and participation, and overlapping regulations governing coastal waste management. This indicates that there is still a gap between existing policies and practices in the field, necessitating improvements such as collaboration among stakeholders, increasing the role of the community in implementing regulations, and increasing infrastructure support from the government.